Supervision in Coaching of Early Childhood Teachers in Sub-District Banda Raya, Indonesia - Niswanto, Niswanto; Fitriani, Fitriani; Murniati, Murniati (Jurnal Pendidikan Progresif, 2020)
Supervision in Coaching of Early Childhood Teachers in Sub-District Banda Raya, Indonesia. Objectives: The purpose of this study was to determine the planning, implementation, and follow-up of the supervision carried out by the supervisors in developing early childhood education teachers in Banda Raya Sub-District, Indonesia. Methods: A descriptive method with a qualitative approach was used in this study. The data needed were collected through observation, interviews, and documentation. The subject of this study consisted of supervisors, principals, heads of teacher working groups, and senior teachers of early childhood education. Findings: The results of this study indicates that (1) the supervision was planned by the supervisors in order to improve the ability of early childhood education teachers in doing their main tasks. In addition, (2) the supervision was conducted through a coordination so that there was no overlapping of the supervision schedules of the school principal and teachers. Finally, (3) this supervision was then followed up with guidance on teachers who encountered obstacles through discussions, case conferences, and question and answer sessions.Keywords: Supervision, early childhood teachers, Indonesia.DOI: 10.23960/jpp.v10.i3.202010